2023
DOI: 10.1093/qjmed/hcad159
|View full text |Cite
|
Sign up to set email alerts
|

New insights into kidney disease after COVID-19 infection and vaccination: histopathological and clinical findings

Abstract: In addition to its pulmonary effects, COVID-19 has also been found to cause acute kidney injury (AKI), which has been linked to high mortality rates. In this review, we collected data from 20 clinical studies on post-COVID-19-related AKI and 97 cases of AKI associated with COVID-19 vaccination. Acute tubular injury was by far the most common finding in the kidneys of patients with COVID-19-related AKI. Among patients hospitalized for COVID-19, 34.0% developed AKI, of which 59.0%, 19.1%, and 21.9% were stage 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 154 publications
0
1
0
Order By: Relevance
“…According to Li Yebei et al. among patients with post-vaccination AKI who undergo kidney biopsy, the most common pathological diagnoses was crescentic glomerulonephritis, followed by acute tubular injury, IgA nephropathy, ANCA-associated vasculitis, minimal change disease, and thrombotic microangiopathy [ 46 ]. Research has identified specific biomarkers of renal injury, including functional biomarkers (Cys C), injury biomarkers (KIM-1, NGAL), and stress biomarkers (TIMP-2 and IGFBP7), which may be beneficial for the early diagnosis of COVID-19 AKI [ 30 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Li Yebei et al. among patients with post-vaccination AKI who undergo kidney biopsy, the most common pathological diagnoses was crescentic glomerulonephritis, followed by acute tubular injury, IgA nephropathy, ANCA-associated vasculitis, minimal change disease, and thrombotic microangiopathy [ 46 ]. Research has identified specific biomarkers of renal injury, including functional biomarkers (Cys C), injury biomarkers (KIM-1, NGAL), and stress biomarkers (TIMP-2 and IGFBP7), which may be beneficial for the early diagnosis of COVID-19 AKI [ 30 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%